2014
DOI: 10.4314/jae.v18i2.4
|View full text |Cite
|
Sign up to set email alerts
|

Constraints to Occupational Diversification among Rural Women in Anambra State, Nigeria

Abstract: The study was carried out in Anambra State, Nigeria to ascertain constraints to occupational diversification among rural women. Questionnaire was used to collect data from a sample of 462 rural women. Percentage, mean scores, standard deviation, factor analysis and student's t-test were used for data analysis. Major constraints to occupational diversification were grouped into labour, institutional, technical and social problems. The study identified solutions to problems to include provision of adequate physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 2 publications
5
6
0
Order By: Relevance
“…This implies that there were more married individuals in farming in the area. This is in line with the findings of Ajani who stated that farming activities are done mostly by people who are married and are responsible enough to take family decisions [14].…”
Section: Resultssupporting
confidence: 91%
“…This implies that there were more married individuals in farming in the area. This is in line with the findings of Ajani who stated that farming activities are done mostly by people who are married and are responsible enough to take family decisions [14].…”
Section: Resultssupporting
confidence: 91%
“…The mean household size was 5.06 with standard deviation of 2. This also corroborates the result of Ajani and Igbokwe (2013) who found that majority of rural women had a household size of 1-5 persons. The lower figure of mean household size of the respondents compared to the average of 6 noted in many studies points out that female headed households are relatively smaller in size than typical traditional male headed rural households.This could account for the labour shortages which are known to limit agriculture in female households thereby promoting non-farm diversification among them.…”
Section: Household Sizesupporting
confidence: 90%
“…Given the poverty situations in rural communities and uncertainties associated with the largely nature-dependent economy of traditional agricultural practice, the need for rural household livelihood diversification is centred on the need for assurance of household food security, generation of additional income, control of available additional income, reduction of poverty and vulnerability among others (Ajani and Igbokwe, 2013). It is also, opined that increased diversity promotes greater flexibility because it allows more possibilities for substitution between opportunities that are in decline and those that are expanding.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, evidence indicates that rural women are innovative, creating something out of nothing to meet the basic needs of their families (Nwoye, 2007; Ajani, 2012; Mbah and Igbokwe, 2015). However, poverty constrains what they can do (Anderson and Obeng, 2017).…”
Section: Poor Women Entrepreneurs In Rural Nigeriamentioning
confidence: 99%
“…Recent studies highlight that women enterprises account for a large proportion of total rural employment and rural income (Mbah and Igbokwe, 2015). Indeed, Ajani (2012) maintains that rural women’s enterprises play major roles in generating income for the rural women.…”
Section: Poor Women Entrepreneurs In Rural Nigeriamentioning
confidence: 99%